Contact, Threat, and Attitudes toward Same-Sex Marriage and Its Beneficiaries. Issue 1 (1st January 2022) - Aberson, Christopher L.; Jett-Dias, Latishia; Clifton, James
Abstract: This study investigated relationships between contact experiences and perceived threat on attitudes toward same-sex marriage and its beneficiaries. Three-hundred and sixty-seven self-identified heterosexual college students completed a series of measures addressing contact experiences (both positive and negative), realistic, and symbolic threat from same-sex marriage, and 8 outcome measures including attitudes toward same-sex marriage, stereotypes, feelings, and emotional reactions. Broadly, findings support intergroup contact theory's proposition that favorable contact experiences relate to less bias. However, propositions regarding negative contact relating to increased bias did not receive support. Results also support intergroup threat theory's proposition that feelings of threat relate to prejudice and that threats demonstrate an indirect effect on the contact-prejudice relationship.